PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI PERSAMAAN REAKSI KIMIA KELAS X IPA SMAN 1 PANGEAN - Alpan Suhari; Edi Kurniawan; Jumriana rahayu Ningsi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
This study aims to develop Student Worksheet (LKPD) Based on Problem Based Learning (PBL) in chemistry learning, the subject of chemical reaction equation which is valid based on validation of material experts, validation of linguists, validation of media experts and validation of student responses. This type of research is Research and development with the 4-D model. The data collection instrument used was a validation sheet. The data analysis technique used is by calculating the percentage score of the validation assessment. The results showed that the Student Worksheet (LKPD) based on Problem Based Learning (PBL) that was developed fulfilled the valid category of 3 material experts, namely 88,76%, 3 media experts 89,05%, 1 linguist which was 94,92%. This learning media also fulfills the valid category which students can use it with 98,56%. Based on this assessment, student worksheet besed problem based learning on chemical reaction equation material are very suitable for use.